IDENTIFIKASI GEN PENYANDI PIREN DIOKSIGENASE PADA ISOLAT BAKTERI PENDEGRADASI PIREN - FA Febria; Jamsari Jamsari; N Nasir; N Nurhidayat (Research Center for Biology-Indonesian Institute of Sciences, 2011)
The pyrene dioxygenase coded by gene is an indicator of bacterial isolates capabilities in pyrene degradation. The encoded gene of pyrene dioxygenase can be amplified and detected in Pseudomonas sp. PyrA2 and Burkholdoriasp. PyrA4 isolates, using primary specific Diox which designed based on PhdF gene sequence, the coding gene of pyrene dioxygenase in Mycobacterium vanbalenii PYR-1. The sequence alignment of pyrene dioxygenase putative gene in both of bacterial isolates with the sequence of pyrene dioxygenase coding gene in M. vanbalenii PYR-1 shows the similarity percentage of 41 % and 42% with Pseudomonas sp. PyrA2 and Burkholdoria sp.PyRA4.